1986
DOI: 10.1007/bf01661308
|View full text |Cite
|
Sign up to set email alerts
|

Ofloxacin, a new quinolone in the treatment of genitourinary and enteric infections

Abstract: During 1984 to 1986, 121 patients with gonorrhoea were treated with ofloxacin. This report is to summarize the results of our trial in patients treated with three different dose regimens of ofloxacin: A) a single 800 mg dose of ofloxacin (32 patients); B) a single 400 mg dose of ofloxacin (55 patients) or C) a twice a day dose of 600 mg ofloxacin (34 patients). In addition, 19 patients with urinary tract infection and eight patients with enteric fever were treated with 400 mg ofloxacin twice a day for seven to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The persistence of infection in all of these subjects suggests that a large proportion of symptomatic N. gonorrhoeae infections that go without treatment are likely to persist at least 14 days. Treatment failures have also been reported in a number of other therapeutic trials that also support the hypothesis that N. gonorrhoeae can infect the lower genital tract and persist in the face of localized inflammatory response for at least 14 days (4, 5). To characterize the average bacterial load during infection, Isbey et al analyzed the urine and semen of men with symptomatic urethritis.…”
Section: Natural History Of Neisseria Gonorrhoeae Infectionmentioning
confidence: 68%
“…The persistence of infection in all of these subjects suggests that a large proportion of symptomatic N. gonorrhoeae infections that go without treatment are likely to persist at least 14 days. Treatment failures have also been reported in a number of other therapeutic trials that also support the hypothesis that N. gonorrhoeae can infect the lower genital tract and persist in the face of localized inflammatory response for at least 14 days (4, 5). To characterize the average bacterial load during infection, Isbey et al analyzed the urine and semen of men with symptomatic urethritis.…”
Section: Natural History Of Neisseria Gonorrhoeae Infectionmentioning
confidence: 68%
“…A number of studies, including one randomized, prospective trial, indicate that ciprofloxacin, ofloxacin and pefloxacin are all effective therapy for typhoid fever and do not result in chronic carriage of the organism (51)(52)(53)(54)(55)). An open trial showed that ciprofloxacin was successful in eliminating fecal excretion from ten of 12 chronic Salmonella typhi excreters, some of whom had excreted the organism for several years; all but two received 28 days of therapy (56).…”
Section: Salmonella In Tections and Chronic Excretion In Addition Tomentioning
confidence: 97%
“…Typhi in Mexico, with nearly 10,000 reported cases and other sporadic outbreaks worldwide in the following two decades made the discovery of novel anti‐ Salmonella drugs even more urgent (Akram et al., 2020; Dyson et al., 2019; Feasey et al., 2015; Kumar et al., 2001; Olarte & Galindo, 1973; Wain et al., 1999). In the next few years, clinicians began prescribing fluoroquinolones (ciprofloxacin, ofloxacin, lomefloxacin and pefloxacin) as potential means of controlling typhoid fever (Eykyn & Williams, 1987; Hafiz et al., 1998; Tanphaichitra et al., 1986). Fluoroquinolones inhibit bacterial DNA gyrase, an enzyme responsible for maintaining the supercoiled state of bacterial genomic DNA (division, coiling and supercoiling) during replication (Cheng et al., 2020; Yu et al., 2020).…”
Section: History Of Antimicrobial Resistance In Salmonella Typhimentioning
confidence: 99%